Study of an arsenic metabolizing bacteria from arsenic contaminated soil of Chandpur district, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2019)
Arsenic is a toxic metal found as inorganic oxyanion arsenate As(V) and arsenite As (III) species. The disposal of toxic heavy metals such as arsenic poses high risk to environment. The present study was undertaken to isolate arsenic-metabolizing bacteria from arsenic contaminated soil of Chandpur district, which is one of the most arsenic contaminated area in Bangladesh and later these bacteria were screened for their ability to metabolize arsenate. Out of ninety eight isolates, ten were found to be capable of metabolizing arsenic in Yeast Extract Mannitol (YEM) medium containing 2 mM arsenate at 37ºC. One of the bacterial isolates designated as I-25 was found to produce an extracellular enzyme which can reduce As(V) into As(III) and able to grow in presence of up to 500 mM arsenate. Subsequent molecular identification of this enzyme producing bacterial isolate using 16s rRNA sequence analysis was correlated with previously identified isolate as Bacillus aryabhatti. Further characterization of the enzyme showed that optimum pH of the extracellular enzyme by the bacterial species was 7 and optimum temperature for the enzyme activity was 60ºC. The bacterial isolates can be exploited for the study of possible bioremediation of arsenic contamination.Jahangirnagar University J. Biol. Sci. 8(1): 57-65, 2019 (June)